Discurso proferido como Paraninfo Geral (UFCG, 2013.2) - Mariz, Saulo Rios (Revista Letras Raras, 2023)
DOI: https://dx.doi.org/10.35572/rlr.v3i1.241 Discurso proferido como Paraninfo Geral (UFCG, 2013.2).